Alzheimer’s Disease 2019
DOI: 10.15586/alzheimersdisease.2019.ch1
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Alzheimer’s Disease as a Brain Expression of a Complex Metabolic Disorder

Abstract: Alzheimer' s disease (AD) is an irredeemable chronic neurodegenerative disorder and the predominant cause of dementia. The disease progression is associated with the deposition of amyloid plaques and formation of neurofibrillary tangles in the brain, yet clinical dementia is the end and culminating stage of the enduring pathology. Recent evidence suggests that AD is characterized by distinctive abnormalities apparent on systemic, histological, macromolecular, and biochemical levels. Besides the well-described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 130 publications
2
27
0
Order By: Relevance
“…Additionally, metabolomics studies of human plasma clearly indicate differentially affected polyamine and arginine metabolism in AD patients. As a result, the subjects with MCI are easily distinguishable from healthy controls and AD patients [ 163 ], which gives hope for AD diagnosis at early stages with routine laboratory blood tests and further supports our perspective on AD as a brain expression of a complex metabolic disorder [ 146 ].…”
Section: Polyamine Pathway In Alzheimer’s Diseasementioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, metabolomics studies of human plasma clearly indicate differentially affected polyamine and arginine metabolism in AD patients. As a result, the subjects with MCI are easily distinguishable from healthy controls and AD patients [ 163 ], which gives hope for AD diagnosis at early stages with routine laboratory blood tests and further supports our perspective on AD as a brain expression of a complex metabolic disorder [ 146 ].…”
Section: Polyamine Pathway In Alzheimer’s Diseasementioning
confidence: 89%
“…Several definite hallmarks of the disease have been described and studied with precision, however, the causal relationships between them and clinical dementia remain to be revealed. Mounting evidence indicates that AD is a pervasive metabolic disorder characterized and possibly caused by dysregulation of numerous biochemical pathways, which underlie its complex pathogenesis [ 146 , 147 ].…”
Section: Polyamine Pathway In Alzheimer’s Diseasementioning
confidence: 99%
“…We demonstrated that norvaline upsurges the hippocampal levels of NOS1 [15] and NOS3 [16]; and therefore, increases the brain NO content. We speculate that the neuroprotective effects of norvaline are mainly mediated by NO generation and the reduction of oxidative stress, which is a principal characteristic of AD [99]. Moreover, NO has been shown to mediate neuronal differentiation of PC12 cells [100].…”
Section: Discussionmentioning
confidence: 91%
“…We demonstrated that norvaline upsurges the hippocampal levels of NOS1 [15] and NOS3 [16]; and therefore increases the brain NO content. We speculate that the neuroprotective effects of norvaline are mainly mediated by NO generation and the reduction of oxidative stress, which is a principal characteristic of AD [79].…”
Section: Discussionmentioning
confidence: 96%